REGISTER F AS A STRATEGY IN CREATING AN ORDERLY ENVIRONMENT IN CLASS IIA SRAGEN PRISON - Martiyanto, Hanida; Soge, Markus Marselinus (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Violation of regulations in correctional institutions is one of the factors in the occurrence of security and order disturbances that hamper the correctional system so that prevention is needed The purpose of this study is to determine Register F as a strategy in creating an orderly environment in Class IIA Sragen Correctional Facility and the obstacles of Register F as a strategy in creating an orderly environment in Class IIA Sragen Correctional Facility. The research conducted used qualitative research methods with data collection techniques of interviews, observations and document studies. The data obtained was then analyzed in a qualitative descriptive way. This research was conducted at the Sragen Class IIA correctional institution which took place from April to October 2024. The first research result shows that the existence of a legal basis in the socialization and implementation of the implementation of register f helps prevent security and order disturbances in sragen prison and there is an increase in security because there are innovations that support the performance of officers and always create a safe and orderly environment as a basis for the running of the correctional system. The second research result is that there are obstacles in the form of a limited number of security resources, limited isolation cells or seclusion cells and less than optimal placement and supervision of CCTV. Keywords: Register F; Prevention; Violation; Safe and Orderly